Peningkatan Kualitas Susu Peternakan Rakyat di Boyolali melalui Program Penyuluhan dan Pendampingan Peternak Sapi Perah - Ardilasunu Wicaksono; Mirnawati Sudarwanto (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2016)
Boyolali District is the center area of dairy farm in Central Java Province. However, the quality of fresh milk of small scale dairy farm was still low due to a low quality of farming practice on hygiene and sanitation. The purpose of this activity was to improve the quality of fresh milk of small scale dairy farm through an extension and guidance of the farmers in using good hygiene and sanitation practices. For this purpose, 10 selecting farmers at Sruni Sub-district and 12 selecting farmers at Lanjaran Sub-district were subjected to intervention of three stages activities. First, collection of preliminary data of the level of hygiene and sanitation on milking process using Blood Agar Swab Test of milking equipment. Second, implementation of extension and advisory intervention. Third, evaluation of the microbiological milk quality based on Total Plate Count (TPC). The results showed that the hygiene and sanitation level of the first condition was considered as a bad category which 60.4% samples of fresh milk were on sixth standard (38.000 microorganism/ml of milk). After implementing extension and advisory intervention, 95.5% samples of fresh milk had a total microbiological number below SNI maximum standard (1.0 x 106 cfu/ml). Only one sample (4.5%) had TPC of 4.4 x 106 cfu/ml. Based on this result, the extension and advisory intervention could be used as a basis approach to increase the quality of fresh milk of small scale dairy farms.